All bets are on: obsession, engagement, and moral tension in sports betting behavior - Yaros, Ronald A. (Frontiers in Psychology, 2025)
IntroductionAs legalized sports betting becomes increasingly integrated into American sports culture—particularly within the NFL—concerns have emerged about how such practices influence fans’ emotional engagement, behavioral dependency, and moral judgment. This study investigates age-based variation in betting behaviors and identifies key predictors of media consumption, perceived dependency, and concern for others’ gambling habits.MethodsA cross-sectional online survey (N= 492) was administered in 2024 using snowball sampling to recruit NFL fans. Branching logic ensured that only those with direct sports betting experience completed all attitudinal questions. Fifteen Likert-scale items measured cognitive, behavioral, and emotional responses to betting. Exploratory factor analysis (EFA) identified latent constructs, and multiple regression models tested four research questions related to fan engagement, moral concern, dependency, and intervention attitudes.ResultsEFA revealed four dimensions: Personal Betting Habits, Betting-Driven Enjoyment, Concern for Others, and Perceived Social Addiction. Perceived obsession with betting was the only consistent and strong predictor of increased sports media engagement. Demographic factors such as age and gender were not significant predictors. Concern for others’ gambling behavior was only weakly related to personal dependency and confrontation attitudes.DiscussionFindings suggest a form of cognitive dissonance among sports bettors, who may recognize problematic behavior in others but refrain from acting on it, especially when they are highly engaged themselves. This study contributes a multidimensional model of betting-related engagement and highlights the need for improved psychometrics, stakeholder awareness, and future longitudinal research on the psychological complexities of sports gambling.